Pengaruh Online Customer Review dan Flash Sale Promotion yang Dimediasi oleh Sikap terhadap Minat Beli Skincare Skintific pada Marketplace Shopee - Wulandari, Nita; Isa, Muzakar (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this study is to examine the impact of online customer reviews and flash sale promotions on purchase interest in skintific skincare products with consumer attitude as a mediating variable Research methodology: Study uses a quantitative approach with closed questionnaire survey techniques. The reseach sample consisted of students from several universities in Surakarta with data analysis carried out using PLS 3.0 Results: The findings reveal that Online Customer Reviews and Flash Sale Promotions have a positive and significant influence on Purchase Interest. Additionally, Consumer Attitude acts as a mediator in the connection between these variables and Purchase Interest. Conclusions: Online Customer Reviews have a positive and significant influence on Purchase Intention, indicating that positive consumer reviews can increase purchase interest. Additionally, Flash Sale Promotions are also proven to have a positive and significant effect on Purchase Intention, showing that sales promotions through flash sale mechanisms are effective in attracting consumer interest. Consumer attitude also plays an important role, as it has been shown to have a positive and significant effect on Purchase Intention. These findings emphasize the importance of customer reviews, flash sale promotions, and consumer attitudes in shaping purchase intention. Limitations: The study lie in the use of only two variable independent, closed questionnaire method and limited sample coverage to students in Surakarta. Contribution: The reseach helps to advance the field of digital marketing strategies, especially in increasing the effectiveness of online promotions and utilizing customer reviews to encourage purchase interest.